Early Immune Response Elicited by Different Trypanosoma cruzi Infective Stages - Brenda Celeste Gutierrez (Frontiers Media S.A., 2021)
Trypanosoma cruzi is a protozoan parasite that affects millions of people in Latin America. Infection occurs by vectorial transmission or by transfusion or transplacental route. Immune events occurring immediately after the parasite entrance are poorly explored. Dendritic cells (DCs) are target for the parasite immune evasion mechanisms. Recently, we have demonstrated that two different populations of DCs display variable activation after interaction with the two infective forms of the parasite: metacyclic or blood trypomastigotes (mTp or bTp) in vitro. The skin constitutes a complex network with several populations of antigen-presenting cells. Previously, we have demonstrated T. cruzi conditioning the repertoire of cells recruited into the site of infection. In the present work, we observed that mTp and bTp inoculation displayed differences in cell recruitment to the site of infection and in the activation status of APCs in draining lymph nodes and spleen during acute infection. Animals inoculated with mTp exhibited 100% of survival with no detectable parasitemia, in contrast with those injected with bTp that displayed high mortality and high parasite load. Animals infected with mTp and challenged with a lethal dose of bTp 15 days after primary infection showed no mortality and incremented DC activation in secondary lymphoid organs compared with controls injected only with bTp or non-infected mice. These animals also displayed a smaller number of amastigote nests in cardiac tissue and more CD8 T cells than mice infected with bTp. All the results suggest that both Tp infective stages induce an unequal immune response since the beginning of the infection.